Consumer Behaviour as a Way to Studying Sociology of Culture - Ahmed, Amar (International Journal of Social and Administrative Sciences, 2020)
As a term, consumption had a monetary and economic presupposition to it and was mainly a sub-field of Marketing under ‘consumer behaviour’. This paper will argue the interdisciplinary aspect to the term by utilizing existing research and then propose possible directions for future research. It will suggest consumer behaviour theory as a way to studying Sociology of Culture. Through reviewing selected research and literature, the paper aims to a) analyse the terms consumption and consumer behaviour; b) connect the terms to the field of sociology and other closely related fields such as anthropology; c) argue the significance of the consumption behaviour to studying cultures and connecting the two terms leading up to Consumer Culture Theory (CCT); and d) offer potential research questions within sociology of culture and cultural sociology using theories consumer behaviour. This paper helps marketing, consumer behaviour, sociology, and cultural studies researchers to understand how cultures influence consumption while, in the same time, consumption constructs cultures.